2005
DOI: 10.31399/asm.cp.istfa2005p0014
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Scanning Laser-SQUID Microscope

Abstract: The scanning laser-SQUID microscope can detect electrical defects in a chip without requiring electrical contacts to the chip. Using our new system, we can get magnetic flux images of a 300mmɸ wafer in air. Experiments with 256Mbit-DRAM chips showed that IDDS testing results are correlated well with laser-SQUID images, and that the spatial resolution is 0.59 µm in an intensity image, and 0.54 µm in a phase image. We have also succeeded in localizing the open site in a whole chip area of a 90nm-node logic IC ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A demonstration of imaging the p-n junctions in a 256 Mbit dynamic random access memory (DRAM) chip using a laser-SQUID showed that the spatial resolution was 0.59 mm in an intensity image, and 0.54 mm in a phase image. 44) This is much better than the resolution obtained using either a similar type of microscopy in the past 45,46) or conventional SQUID microscopy [47][48][49][50] (Fig. 12).…”
Section: Scanning Laser-squid For Ic Testingmentioning
confidence: 83%
See 2 more Smart Citations
“…A demonstration of imaging the p-n junctions in a 256 Mbit dynamic random access memory (DRAM) chip using a laser-SQUID showed that the spatial resolution was 0.59 mm in an intensity image, and 0.54 mm in a phase image. 44) This is much better than the resolution obtained using either a similar type of microscopy in the past 45,46) or conventional SQUID microscopy [47][48][49][50] (Fig. 12).…”
Section: Scanning Laser-squid For Ic Testingmentioning
confidence: 83%
“…The intensity and phase of the magnetic flux detected by the SQUID magnetometer are imaged. 1,44) The spatial resolution of the laser-SQUID is much better than conventional SQUID microscopy because it is limited by the laser beam diameter and not the size of the SQUID detector or the distance between the detector and the sample (Fig. 11).…”
Section: Scanning Laser-squid For Ic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…For failure analysis, the failure sites of the 20-link test structures were detected by the optical-beam-induced resistance change (OBIRCH) method. 9,11) Cross sections of the failed vias were prepared using a focused ion beam (FIB) and observed by scanning electron microscopy (SEM).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In order to retain and upgrade the reliability of semiconductor devices, failure analysis is often carried out to identify the causes of faults in the semiconductor devices. In the failure analysis, the optical beam induced resistance change (OBIRCH) [1][2][3] method is recognized as a powerful technique to localize the faults of metal interconnections [4][5][6][7][8][9][10] in a semiconductor device.…”
Section: Introductionmentioning
confidence: 99%